Methodological Foundations of the Development of Professionally-Oriented Sociocultural Competence of a Foreign Language Teacher Using the Newspaper Material - Halyna V. Prystai (Mukachevo State University, 2021)
The paper covers the features of development and improvement of sociocultural knowledge, skills and abilities of future foreign language teachers in the development of their professionally-oriented sociocultural competence. The relevance of the study is determined by the necessity to analyse the methods of using newspaper publications in the process of mastering sociocultural knowledge and forming sociocultural skills of philology students. The purpose of the study is to cover the features of applying the methodology for forming the sociocultural competence of a future English teacher through the use of newspaper material. In the process of study, the method of critical analysis of scientific literature was applied; the method of studying and generalising the experience of teachers; the method of theoretical analysis and synthesis in identifying the linguistic and stylistic features of English-language newspaper texts, in the process of analysing the principles and criteria for selecting newspaper articles, as well as to characterise the types of reading according to the communicative goals and stages of working with the text; the method of systematisation and generalisation in the study of research results. It was identified that the involvement of elements of the language culture of the people whose language is being studied in the content of learning is facilitated by Mass Communication Media, in particular newspapers. It was reasoned that newspaper articles provide the development of foreign language communicative competence, enriching the student's vocabulary, improving his skills and abilities in reading and speaking. It was proved that the tasks compiled based on newspaper material contribute to the creation of an authentic sociocultural space, develop students' ability to analyse patterns of speech behaviour in their native and foreign languages, improve their communicative skills and language competence, deepen background knowledge, and increase motivation to learn. The scientific novelty of the results lies in the detailed description of the requirements for exercises of the sociocultural direction, and their practical significance lies in the possibility of applying the results of the study in teaching a foreign language in the higher educational institutions